Three-month effect of Silver Diamine Fluoride (SDF) in Salivary Levels of Streptococcus Mutans in children. An exploratory trial - Garrastazu, Marta Diogo; Mathias-Santamaria, Ingrid Fernandes; Rocha, Rafael Santos [UNESP]; Diniz, Michele Baffi; Caneppele, Taciana Marco Ferraz [UNESP]; Bresciani, Eduardo [UNESP] (My University, 2020)
Purpose: The aim of this exploratory trial was to compare the 3-month effect of two antimicrobials on the salivary levels of Streptococcus mutans (SM) in children. Materials and Methods: Ninety school children aged 6-10 years participated. They were divided into two groups according to treatment used: 1% chlorhexidine gel (CHX) or 30% silver diamine fluoride (SDF). Saliva for SM colony forming unit (CFU)/ml counting was harvested in four periods: baseline (prior to antimicrobials); P1 (24 h after antimicrobial therapy); P30 (30 days after antimicrobial therapy); and P90 (90 days after antimicrobial therapy). CFU/ ml data was submitted to repeated measures by analysis of variance (ANOVA). Results: Only the time factor influenced the results (p <0.001), with a reduction of SM for all evaluated periods in comparison to the baseline. No influence of antimicrobials or interactions of factors were detected (p >0.05). P30 presented the lowest levels of SM and at P90, SM levels were similar to P1 but still lower than the baseline observations. SDF and CHX presented a similar effect on SM within each period of evaluation (p = 0.65). Conclusion: It was concluded that 30% SDF presents similar antimicrobial effects as 1% CHX over time. SDF might be used as an adjunctive therapy for controlling dental caries in children.
Keywords: Dental caries; Silver diamine fluoride; Streptococcus mutans